Avaliação da atividade antitumoral e toxicidade do Trachylobano-360 de Xylopia langsdorffiana St. Hil. & Tul. (Annonaceae) - Pita, João Carlos Lima Rodrigues (2010)
Cancer is a disease of the genome of our cells and experimental oncology is valuable to study the various aspects related to neoplastic processes. Many drugs currently used in chemotherapy have been isolated from species of plants or derived from natural prototype. Nevertheless, medicinal plants have aggressive substances, and for this reason, their toxicity should be assessed. Xylopia langsdorffiana is a tree popularly known as pimenteira-da-terra . Their phytochemical study characterized mainly diterpenes, with important biological activities. Diterpenes of the trachylobane type are rare in the plant kingdom, and, therefore, still have few studies of biological activities. In previous studies, the ent-7-acetoxytrachylobane-18-óic acid (trachylobane-360), obtained from Xylopia langsdorffiana, showed activity in vitro, which aroused the interest to investigate their possible antitumor activity in vivo. Thus, this study aimed to evaluate the antitumor activity and toxicity of trachylobane-360 through in vitro and in vivo assays. Initially, a pharmacological screening of twenty-one natural products, was performed against sarcoma 180 cell line, where the most cytotoxic were trachylobane-360, the ent-7-hidroxytrachylobane-18-óic acid (trachylobane-318) and the essential oil from leaves of X. langsdorffiana (O.E.X). IC50 values obtained from the tests of trypan blue exclusion and MTT reduction were, respectively, 54,28 and 53,28 μg/mL for trachylobane-360, 100,8 and 104,0 μg/mL for trachylobane-318 and 206,4 and 209,3 μg/mL for O.E.X. The trachylobane-318 was isolated in small quantities, being execution impossible of later cytotoxicity assays (Artemia salina and hemolysis). LC50 values obtained in bioassays with A. saline for trachylobane-360 and O.E.X. were, respectively, 245.3 and 10.05 μg/mL. CH50 values obtained in the experiment of cytotoxicity in erythrocytes (hemolysis), for trachylobane-360 and OEX were, respectively, 98.50 and 742.4 μg/mL. To evaluate the in vivo antitumor activity against sarcoma 180 was used trachylobane-360, because it was the most active in preliminary tests. The rates of inhibition of tumor growth were 45.60 and 71.99 % for treatment with trachylobane-360, 12.5 and 25 mg/kg, respectively, with no significant difference between the inhibition caused by the higher dose of this when compared to treatment with 5-FU (positive control). The toxicological analysis of the animals showed that the use of trachyloban-360 did not change spleen and thymus index, or the hematological parameters compared with mice-bearing, these changes occur with chemotherapeutic drugs used in clinical practice. Moreover, the trachylobane-360 did not modify liver index, nor it cause extensive microscopic changes in the heart, liver and kidneys of animals, corroborating with the biochemical parameters, wich remain unchanged. Necrosis area extensive, on tumors of different groups was observed, accompanied by a reduction in the number of mitoses, being these effects more pronounced after treatment with 25 mg/kg of trachyloban-360. Therefore, it is possible to infer that the trachyloban-360 has significant antitumor activity and low toxicity, this essential balance to its applicability as a pharmacological drug.